On history - Braudel, Fernand (The university of Chicago, 1980)
The first English translation of Ecrits sur l'histoire—a collection of essays written over a twenty-year period following publication of Braudel's masterwork, La, Méditerranée—On History sets forth Braudel's reflections on the intellectual framework of his historical studies. Braudel calls on the historian to penetrate beneath the surface of political events to uncover and measure the forces shaping collective existence. Cycles of production, wages and prices, grids of communication and trade, fluctuations and climate, demographic trends, popular beliefs—all of these phenomena are proper subjects of the historian's investigations. It is only through study of the longue durée, Braudel argues, that one can discern structure, the supports and obstacles, the limits and his experience cannot escape.